1991
DOI: 10.1080/02652039109373967
|View full text |Cite
|
Sign up to set email alerts
|

Contents ofFusariumtoxins in Finnish and imported grains and feeds

Abstract: The aim of the present study was to investigate the levels of trichothecenes in representative samples of Finnish and imported cereals and feeds from the 1987 and 1988 crops. Trichothecene concentrations were determined in samples as trimethylsilylether derivatives by a gas chromatograph equipped with a mass selective detector (GC-MSD) using selected ion monitoring (SIM) which proved to be a reliable and sufficiently sensitive technique. Representative samples of Finnish and imported oats, wheat, barley, rye, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 13 publications
2
25
2
Order By: Relevance
“…100 µ l N-trimethylsilylimidazole (TMSI) reagent was added to the residue evaporated to dryness. DON, DAS, 3-acetyldeoxynivalenol (3-AcDON), FX, NIV, T-2 and HT-2 toxins and 19-nortestosterone (the internal standard) were identified and quantified as trimethylsilylether derivatives, employing GC-MS (Rizzo et al 1986, Hietaniemi and Kumpulainen 1991, Saastamoinen and Saloniemi 1997.…”
Section: Sample Clean-up Identification and Quantificationmentioning
confidence: 99%
See 4 more Smart Citations
“…100 µ l N-trimethylsilylimidazole (TMSI) reagent was added to the residue evaporated to dryness. DON, DAS, 3-acetyldeoxynivalenol (3-AcDON), FX, NIV, T-2 and HT-2 toxins and 19-nortestosterone (the internal standard) were identified and quantified as trimethylsilylether derivatives, employing GC-MS (Rizzo et al 1986, Hietaniemi and Kumpulainen 1991, Saastamoinen and Saloniemi 1997.…”
Section: Sample Clean-up Identification and Quantificationmentioning
confidence: 99%
“…Natural toxins, such as mycotoxins, have emerged as a significant factor affecting the safety image of cereal grains as a raw material for the food and feed industry. Many previous studies in Finland (Karppanen et al 1985, Hietaniemi and Kumpulainen 1991, 1993, Rizzo 1993) and other European countries (Tanaka et al 1988, Langseth et al 1989, Müller and Schwadorf 1993, Pettersson et al 1995, Widestrand 2001, Döll et al 2002, Schollenberger et al 2002 as well as globally (Tanaka et al 1988, Shephard et al 1996, Groves et al 1999, Janardhana et al 1999, Salay and Mercadante 2002 have shown that there is reason to focus on Fusarium toxins and their appearance. A planned European Union directive will specify the maximum limits for trichothecenes such as 4-deoxynivalenol (DON), T-2 toxin and HT-2 toxin and for zearalenone (ZEN) and fumonisins.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations